The analysis of material removal rate of WEDM miniature gears - Goyal, Ashish (Array, 2021)
Gear fabrication in wire electrical discharge machining (WEDM) plays an important role in manufacturing industries. This paper describes the analysis and optimization of process parameters for the fabrication of spur gear on brass spur gear on brass workpiece (10cmx15cmx6mm) material by wire EDM process. The experiments were performed by using the design of experiment (DoE) approach and the material removal rate (MRR) was analyzed by response surface methodology technique. The effect of input parameters i.e. pulse on time, pulse off time and feed rate on MRR has been investigated. The surface geometry of the gears has been analysed by the Scanning Electron Microscopy (SEM). This study found that 0.4 μs for pulse on time, 60 μs for pulse-off time and 6 mm/min for feed rate provides improved material removal rate. The analysis of variance shows that pulse on time and feed rate are the significant parameters for the wire EDM process. The SEM image exhibits the capability of WEDM to machined miniature gear with a uniform distribution of regular-shaped craters and defect-free flank surface.